Pengaruh Arus Kas Bebas, Profitabilitas, dan Ukuran Perusahaan Terhadap Kebijakan Utang - Rizanti, Puti Zhafira; Gurendrawati, Etty; Respati, Dwi Kismayanti (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
Free Cash Flow, Profitability, and Company Size as factors influencing Debt Policy in LQ45 companies listed on the Indonesia Stock Exchange (BEI) during the fiscal year 2021-2023. The purpose of this study was to ascertain how debt policy is impacted by free cash flow, profitability, and firm size. The population of this study is the LQ45 firms that were listed for the 2021-2023 term on the Indonesia Stock Exchange (BEI). Financial records that are accessible on the IDX website provide the data for this study methodology, which employs quantitative techniques. Purposive sampling was used to choose the sample, and 108 observation data were obtained. The SPSS program was used to process the data and multiple linear regression analysis was used to evaluate it. The analysis’s findings support the notion that debt policy is not significantly impacted by profitability. In the meanwhile, the size of the organization and free cash flow have a big impact on debt strategy.